Awareness about breast cancer and mammogram among women attending outpatient clinics, Ain Shams University Hospitals, Egypt - Ayat F. Manzour; Dina A. Gamal Eldin (SpringerOpen, 2019)
Abstract Background Breast diseases in women, whether benign or malignant, are very commonly encountered. The breast is the commonest site for female cancer in Egypt (38.8%). Breast cancer screening can reduce morbidity and mortality and improve the survival rate for this malignancy. Mammogram can be used as a screening technique beside its role as diagnostic, especially in women over 40 years of age. Objectives To assess knowledge, attitude and practice regarding breast cancer and awareness about mammogram as a screening method among a group of females attending Ain Shams University outpatient clinics. Methods A cross-sectional study was performed from August to September 2017. A systematic random sample was taken from attending females (18-70 years) in Ain Shams University outpatient clinics (Internal Medicine, Surgery, Pediatrics Hospital, and Maternity hospital). They were interviewed using a questionnaire inquiring about sociodemographic background, participants' knowledge, attitude, and practice towards breast cancer and its screening. Results The mean age ± SD of attending females (18-70 years) was 37 ± 11 years. Most study participants had correct information about mammography. They showed poor knowledge level about risk factors. Mass media such as TV and internet were identified as the main source of information on breast cancer by 43% and 23.9%, respectively. In general, participants had positive attitude towards breast cancer screening by mammography. Around 90% agreed that mammogram was the best way to find a very small lump in the breast, and 91.4% agreed that women who have regular screening by mammogram have better disease outcome than those who do not screen. Regarding mammography practice rate, a small percent of participants (8.1%) was advised by their doctors to conduct a screening mammography. The level of knowledge was significantly and positively correlated with their attitude towards breast cancer screening. Conclusion The poor knowledge and practices of women illustrate the need for health education program directed to Egyptian females to improve their knowledge about breast cancer-especially its risk factors-and its screening. Using TV and Internet as media for spreading information about this disease is crucial.